Tuberous Sclerosis Complex: Prenatal Diagnosis Using Ultrasound and Magnetic Resonance Imaging—A Report of Two Cases - Santana, Eduardo Félix Martins; Esteves, Ana Maria Faria; Delorenzo, Daniella Guerra; Hygino, Celso; Werner, Heron; Araujo Júnior, Edward (Indian Journal of Radiology and Imaging, 2022)
Tuberous sclerosis complex (TSC) is a multiple system neurocutaneous syndrome with a genetic disorder caused by different mutations in TSC1 or TSC2. Usually, TSC causes tumors in the heart, brain, kidneys, eyes, and lungs. However, tumors can also develop in any other organs. The prenatal diagnosis of TCS is based on the identification of fetal cardiac tumors by ultrasound and brain subependymal nodules, usually identified by fetal magnetic resonance imaging (MRI). We present two case reports of the prenatal diagnosis of TCS using both ultrasound and MRI, which were confirmed by clinical and radiological methods in the postnatal period accordingly.
Keywords: prenatal diagnosis; tuberous sclerosis complex; ultrasound; magnetic resonance imaging